2019
DOI: 10.1186/s12864-019-6270-4
|View full text |Cite
|
Sign up to set email alerts
|

Combining information from genome-wide association and multi-tissue gene expression studies to elucidate factors underlying genetic variation for residual feed intake in Australian Angus cattle

Abstract: BackgroundGenome-wide association studies (GWAS) are extensively used to identify single nucleotide polymorphisms (SNP) underlying the genetic variation of complex traits. However, much uncertainly often still exists about the causal variants and genes at quantitative trait loci (QTL). The aim of this study was to identify QTL associated with residual feed intake (RFI) and genes in these regions whose expression is also associated with this trait. Angus cattle (2190 steers) with RFI records were genotyped and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 87 publications
0
13
0
2
Order By: Relevance
“…Of these, we identified several genes to be related to body conformation, meat quality, susceptibility, and reproductive efficiency. For instance, BCKDHB was found to be related to the attachment width in Chinese Holstein cattle [52], and this gene was also reported to display a significant expression associated with RFI in Australian Angus cattle [53]. MAB21L1 were detected with a higher expression in longissimus lumborum and psoas major [54], which may result in distinct metabolic patterns and physiological processes for meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, we identified several genes to be related to body conformation, meat quality, susceptibility, and reproductive efficiency. For instance, BCKDHB was found to be related to the attachment width in Chinese Holstein cattle [52], and this gene was also reported to display a significant expression associated with RFI in Australian Angus cattle [53]. MAB21L1 were detected with a higher expression in longissimus lumborum and psoas major [54], which may result in distinct metabolic patterns and physiological processes for meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…The BovineHD1400007035-rs136017102 SNP on Chr14, located close to the XKR4 gene, in previous studies, was reported to be associated with feed intake and growth phenotypes in cattle [ 75 ], residual feed intake in Australian Angus cattle [ 76 ], carcass weight (CWT) and eye muscle area (EMA) in Korean Hanwoo cattle [ 77 ], carcass trait [ 78 ], fat deposition in genome-wide association study for carcass trait in Brazilian Nellore cattle [ 79 ] and subcutaneous rump fat thickness in indicine and composite cattle [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…VEPH1 influenced other cattle conformation traits such as udder cleft in Holstein and rump fat thickness in Nellore cattle, reflecting its role in lipid metabolism [78,79]. Furthermore, recent studies observed an association of VEPH1 with residual feed intake and antibody response to parasites in cattle [80,81].…”
Section: Multi-breed Gwas For Conformation Traits and Functional Annomentioning
confidence: 99%